2023
DOI: 10.1002/qj.4480
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of the low‐level jets observed over Dunkerque (North Sea French coast) using 4 years of wind lidar data

Abstract: This study investigates the occurrence and characteristics of low‐level jets (LLJs) up to 200 m above sea level in the North Sea area, specifically in the southernmost part of the basin, at the entrance of the English Channel. Using a short‐range Doppler lidar installed in Dunkerque Port, on the northern coast of France, wind profiles were recorded for 4 years and analyzed statistically. LLJs were detected on more than 11,000 of the 10‐min average wind profiles (5% of time), with similar jet core height and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 75 publications
(126 reference statements)
0
5
0
Order By: Relevance
“…Furthermore, the climatology of LLJs around the islands of Great Britain and Ireland is unknown. A recent study by Dieudonné et al (2023), at Dunkerque, a coastal location to the English Channel, found LLJs occur on average around 5% of the time during year; occurring mostly during the late night (0000 to 0700 UTC) and the afternoon (1200 to 1800 UTC); and during the spring and summer periods, when they are at their most intense, with a frequency two to three times greater than that of the autumn and winter periods. Our case studies appear to be consistent with these observations.…”
Section: Analysis Of Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Furthermore, the climatology of LLJs around the islands of Great Britain and Ireland is unknown. A recent study by Dieudonné et al (2023), at Dunkerque, a coastal location to the English Channel, found LLJs occur on average around 5% of the time during year; occurring mostly during the late night (0000 to 0700 UTC) and the afternoon (1200 to 1800 UTC); and during the spring and summer periods, when they are at their most intense, with a frequency two to three times greater than that of the autumn and winter periods. Our case studies appear to be consistent with these observations.…”
Section: Analysis Of Resultsmentioning
confidence: 98%
“…Baroclinic (Holton, 2004) LLJs, such as coastal and ice-edge LLJs, are formed due to horizontal temperature differences that arise from differential heating and cooling of adjacent surfaces. This creates shallow frontal zones, and hence vertical wind shear, at the boundary between land-sea and ocean-ice (Beardsley et al, 1987;Chechin & Lüpkes, 2019;Dieudonné et al, 2023;McNider & Pielke, 1981). Similarly, valley LLJs are created by differential heating of sun-facing sloped terrain and shaded valleys in mountainous regions (Holton, 1967).…”
Section: Introductionmentioning
confidence: 99%
“…At the CTC site, an 11 m tower was outfitted with temperature and chemical sensors, and another set of sensors was placed on the roof of the building at 23 m AGL to probe the role of the near-surface temperature inversion in trapping pollution. A Doppler wind lidar (Vaisala WindCube v2), 90 which probed wind fields 40–300 m AGL, was located at the CTC site for the first half of the study. UCLA’s long-path differential optical absorption spectrometer (LP-DOAS) used spectroscopy to measure path-averaged pollutant concentrations (O 3 , NO 2 , SO 2 , HCHO, and HONO) from its base in a parking garage at 64.844°N, 147.716°W, which is 610 m ENE of the CTC building.…”
Section: Experimental/methodsmentioning
confidence: 99%
“…At the CTC site, an 11 m tower was outfitted with temperature and chemical sensors, and another set of sensors was placed on the roof of the building at 23 m AGL to probe the role of the near-surface temperature inversion in trapping pollution. A Doppler wind lidar (Vaisala WindCube v2), 90 The above sites were picked to be near the downtown site and the house site to sample pollution related to urban pollution problems and surrounding near-downtown residential neighborhoods. To sample air further aloft, a tethered balloon was deployed in a large open farm field to the west of downtown.…”
Section: ■ Introductionmentioning
confidence: 99%
“…In France, the LLJ has been observed in northern coastal urban areas (Roy et al, 2021(Roy et al, , 2022Dieudonné et al, 2023), but coastal jets usually present different formation mechanisms and characteristics than those observed inland. This is mainly explained due to the importance of the sea-land breeze interactions (Karipot et al, 2009).…”
Section: Introductionmentioning
confidence: 99%